1978
DOI: 10.1159/000136786
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Calcium, Prostaglandins and Indomethacin on the Smooth Muscle of the Bladder

Abstract: The effects of prostaglandin (PG) E2, PGF and indomethacin (Indo) were studied on isolated detrusor smooth muscle strips in balanced salt solution and in 80 mΛf K+ depolarizing solution. The addition of Indo to the smooth muscle preparation at concentrations of 0.1 to 1.0 μM produced depression of spontaneous motility that was partially antagonized by PGE2 or by elevating the extracellular Ca2+ level. Alone, both PGE2 and Ca2+ cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The present study is the first to show that rabbit bladder ICCs constitutively express both COX-1 and COX-2, and that selective COX-1 and COX-2 inhibition can exert a potent and highly efficacious inhibition of SRC. These results support and extend earlier reports that indomethacin and other non-selective COX inhibitors reduce SRC in bladder strips isolated from several mammalian species [29,57]. The precise prostaglandin species responsible for initiating SRC was not determined in this study.…”
Section: Discussionsupporting
confidence: 87%
“…The present study is the first to show that rabbit bladder ICCs constitutively express both COX-1 and COX-2, and that selective COX-1 and COX-2 inhibition can exert a potent and highly efficacious inhibition of SRC. These results support and extend earlier reports that indomethacin and other non-selective COX inhibitors reduce SRC in bladder strips isolated from several mammalian species [29,57]. The precise prostaglandin species responsible for initiating SRC was not determined in this study.…”
Section: Discussionsupporting
confidence: 87%
“…It is known that transmembrane Ca2 + -influx plays an essential role in the maintenance of tone and spontaneous contractility and also in the activation of contractions induced by a variety of stimulants in mammalian and human bladders Maggi etal., 1982;Khanna etal., 1983), since these contractile activities are inhibited by Ca2 + entry blockers. In particular, several investigators have demonstrated the inhibitory effect of nifedipine (Ca2 + -entry blocker) or Ca2 + -free medium on the prostaglandin induced contractions in rabbit and human detrusor muscle (Anderson & Kohn, 1978;Forman et al, 1978). It has been suggested that prostaglandins may serve as regulators of Ca2 + binding sites within the cell membrane and thereby modify cell motility (Paton & Daniel, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that prostaglandins may serve as regulators of Ca2 + binding sites within the cell membrane and thereby modify cell motility (Paton & Daniel, 1967). Anderson & Kohn (1978) suggested that prostaglandins may act at Ca2 + channels to augment the movement of Ca2 -through membranes or that they might serve a role as carrier for Ca2 + in the rabbit detrusor muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results may suggest that, in rat atria, veratridine may activate Ca2+ influx across membranes due to the increase in the products of cyclooxygenase pathways. Further, it has been suggested that prostaglandins may act as Ca2+ channels to augment the movement of Ca2+ influx through membranes or that they might serve a role of carrier for Ca2+ in the tissues [8][9][10][11]. These results suggest that veratridine may increase the release of arachidonic acid and subsequently activate the synthesis of pros taglandins, which in turn increase Ca2+ in flux, resulting in the positive inotropic ac tion.…”
Section: Discussionmentioning
confidence: 99%